2014
DOI: 10.1186/1475-2840-13-78
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation endproducts trigger autophagy in cadiomyocyte Via RAGE/PI3K/AKT/mTOR pathway

Abstract: MethodsRat neonate cardiomyocytes were cultured and treated with AGEs at different concentration. Two classic autophagy markers, microtubule-associated protein 1 light chain 3 (LC3) and Beclin-1, were detected by western blot assay. The inhibition of RAGE and phosphatidylinositol 3-phosphate kinase (PI3K)/Akt/mTOR pathway were applied to cells, respectively.ResultsAGEs administration enhanced the expression of Beclin-1 and LC3 II in cardiomyocytes, increased the number of autophagic vacuoles and impaired the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 36 publications
(36 reference statements)
5
101
1
Order By: Relevance
“…There is a strong link of rapidly altered metabolic activity induced by target inhibition of the IGF-1R signaling pathways in proliferating cells. Through direct interaction with IGF1Rβ, SM22α overexpression enhances tumor cell growth and activates the IGF1R/PI3K/Akt pathway [30,31]. Our results show that IGF2R also regulates cell proliferation, apoptosis, migration, and invasive ability.…”
Section: Discussionmentioning
confidence: 78%
“…There is a strong link of rapidly altered metabolic activity induced by target inhibition of the IGF-1R signaling pathways in proliferating cells. Through direct interaction with IGF1Rβ, SM22α overexpression enhances tumor cell growth and activates the IGF1R/PI3K/Akt pathway [30,31]. Our results show that IGF2R also regulates cell proliferation, apoptosis, migration, and invasive ability.…”
Section: Discussionmentioning
confidence: 78%
“…SIRT3 is overexpressed to a greater extent in several human oral cancer cells and tissues than in normal controls, and SIRT3 downregulation in these cells inhibited oral cancer cell growth and proliferation and enhanced radio- and chemo-therapeutic drug cytotoxicity [19]. High expression of SIRT3 is associated with a shorter survival time in esophageal cancer patients [20,21]. p53-induced growth arrest in human bladder cancer is regulated by the mitochondrial SIRT3 deacetylase [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Hou et al reported that AGEs increase both the number of autophagosomes in endothelial cells and cell death (66). Inhibition of autophagy, however, enhanced AGE-mediated cell death in endothelial cells (155), suggesting that autophagy is functioning to protect against AGE-mediated cellular damage.…”
Section: Autophagy In Cell Types Beyond the Cardiomyocytementioning
confidence: 99%